2019
DOI: 10.1039/c8tx00298c
|View full text |Cite
|
Sign up to set email alerts
|

A review of arsenic exposure and lung cancer

Abstract: As a well-established human carcinogen, arsenic has increased the risk of lung cancer over the past decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 93 publications
1
26
0
Order By: Relevance
“…This means that almost no oAs was converted into iAs under the experimental condition. It is consistent with previous study (Wei et al, 2019). The result further showed that uAs may bind to proteins in the form of iAs.…”
Section: Discussionsupporting
confidence: 94%
“…This means that almost no oAs was converted into iAs under the experimental condition. It is consistent with previous study (Wei et al, 2019). The result further showed that uAs may bind to proteins in the form of iAs.…”
Section: Discussionsupporting
confidence: 94%
“…The DDR system encompasses eight pathways: MMR, BER, checkpoint factors, Fanconi anemia, HRR, NER; nonhomologous end-joining; and DNA translesion synthesis. (Faita et al 2013;Lau et al 2013;Rao et al 2017;Wei et al 2019) Skin Cancer 5-FUl, 5% imiquimod 2,3-dimercapto-l-propanesulfate (Guha Mazumder et al 2001;Khandpur and Sharma 2003;Yu et al 2006)…”
Section: Dna Damage and Repair Biomarkers In Cancer Therapymentioning
confidence: 99%
“…This exposes the big problem of how these toxins are incorporated into the food chain, causing a phenomenon of bioaccumulation and biomagnification so that the final amount to which a human is exposed by consumption of food and water contaminated with the metal is greater, and with them, there would be a greater risk of developing cancer due to arsenic [98,6]. Prolonged exposure to high concentrations of arsenic is linked to a greater risk for cancer of the bladder, skin, lung, digestive pathways, liver, kidney and lymphatic and hematopoietic cancers [98,109,110,6,17,18].…”
Section: Environmental Toxins Foods and Cancermentioning
confidence: 99%